2019
DOI: 10.5688/ajpe7327
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacotherapy Scholars Program to Provide Intensive Training to Enhance Pharmacy Students’ Postgraduate Readiness

Abstract: Objective. To design, integrate the curriculum for, and evaluate an innovative program to facilitate placement of students into postgraduate pharmacy residency training programs involving direct patient care. Methods. The Pharmacotherapy Scholars Program (PSP) was designed to prepare fourth-professional year students to become highly proficient in a direct patient care role and to successfully match with postgraduate residency training programs. The following elements were included in the year-long curriculum:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 17 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…For institutions seeking to have their trainees perform some or all of the analyses, successful programs and/or research mentors may provide research fundamental sessions in data collection and analysis with hands-on training, empowering the trainee to perform the statistical analyses for their project and appropriately interpret and accurately communicate results. 18,19,24,27,33,35,39,41,[53][54][55][56] There are also free tutorials and resources online that the trainee may use to learn how to perform the statistical analyses for their project. For institutions seeking to provide support to their trainees for data analysis, schools of pharmacy and residency programs associated with academic institutions or through collaborations may be able to engage faculty, data analysts, or graduate students with expertise in biostatistics or qualitative analysis to support the trainee.…”
Section: Length Of Time To Initiate a Research Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…For institutions seeking to have their trainees perform some or all of the analyses, successful programs and/or research mentors may provide research fundamental sessions in data collection and analysis with hands-on training, empowering the trainee to perform the statistical analyses for their project and appropriately interpret and accurately communicate results. 18,19,24,27,33,35,39,41,[53][54][55][56] There are also free tutorials and resources online that the trainee may use to learn how to perform the statistical analyses for their project. For institutions seeking to provide support to their trainees for data analysis, schools of pharmacy and residency programs associated with academic institutions or through collaborations may be able to engage faculty, data analysts, or graduate students with expertise in biostatistics or qualitative analysis to support the trainee.…”
Section: Length Of Time To Initiate a Research Projectmentioning
confidence: 99%
“…Many published research and scholarship training programs also describe the use of a research advisory-type group to review the project options to determine feasibility, novelty, rigor, and impact prior to becoming available to trainees. 18,19,39,45,46,54 grams is dependent on the local infrastructure, resources, and goals of each institution. Additionally, residency programs tend to be more constrained by time limits of programs and not all residency programs may be affiliated with universities in which they are able to utilize academic resources and/or personnel.…”
Section: Selection Of Research Project That Lacks Rigor Depth or Feasibilitymentioning
confidence: 99%
“…During APPEs, students should be provided with opportunities to explore career options, practice interviewing, prepare and review curriculum vitae, practice presentations, and get involved in projects or research. For example, C/SOPs have developed specific postgraduate training tracks to enhance student preparation and strength of application for residency or fellowship placement 32 . Enhancing graduation readiness can also involve licensure examination preparation or assessments that are incorporated into APPEs or provided in a concentrated program after APPEs, but before graduation 33 …”
Section: Outcomes Preparedness and Readinessmentioning
confidence: 99%
“…10 The lack of evidence may be due to the term "intensive", which could mean time-reduced/accelerated or rigorous; the term and definition is crucial. [10][11][12] For example, one study found that an intensive Pharmacotherapy Scholars Program for fourth year pharmacy students resulted in high residency placement rates and significant improvements to knowledge and clinical skills, however, this intensive course was a year-long program that focused on rigor. 11 Intensive or accelerated teaching is defined as being offered in less time or fewer contact hours than normal and studies have shown that compared to traditional formats there is no difference in outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For example, one study found that an intensive Pharmacotherapy Scholars Program for fourth year pharmacy students resulted in high residency placement rates and significant improvements to knowledge and clinical skills, however, this intensive course was a year-long program that focused on rigor. 11 Intensive or accelerated teaching is defined as being offered in less time or fewer contact hours than normal and studies have shown that compared to traditional formats there is no difference in outcomes. 12, 13 Harwood and colleagues found no statistically significant differences on student performance (final assignments or course grades) and student satisfaction (course evaluation ratings) in an intensive (7-week) course compared to traditional semester long course (15-week) in three graduate health science programs.…”
Section: Introductionmentioning
confidence: 99%